The Importance of Positive Affect: The Role of Affective Personality in Predicting Organizational Citizenship Behavior - Ramdhani, Neila; Ancok, Djamaludin; Adrianson, Lillemor (UI Scholars Hub, 2017)
Previous research demonstrates inconsistent results in predicting how affect influences organizational citizenship behavior (OCB). This study aims to solve the inconsistency by taking the position that positive affect and negative affect are orthogonal, and their interaction produces four types of affective personality. They are ‘Self-fulfilling’ (high positive affect and low negative affect), ‘High affective’ (high positive affect and high negative affect), ‘Low affective’ (low positive affect and low negative affect) and ‘Self-destructive’ (low positive affect and high negative affect). The study hypothesizes that the self-fulfilling group displays the highest mean of OCB while the self-destructive displays the lowest. The high affective and low affective groups lie somewhere in between the two groups. The participants of this study were 227 employees, consisting of 151 males and 76 females with ages ranging from 20 to 60 years old (mean=38). They were measured using the Organizational Citizenship Behavior Scale (OCBS) and Positive and Negative Affect Schedule (PANAS). Based on the scores of their positive and negative affect dimensions, they were classified into four groups of affective personality types. One-way ANOVA analysis supported the hypothesis. The selffulfilling group revealed the highest mean of Organizational Citizenship Behavior while the Self-destructive group revealed the lowest. The High affective and Low affective groups were located in between the first two groups. This paper discusses this contribution and highlights how it is potential to explain organizational behavior.